1984
DOI: 10.1677/joe.0.1020033
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of corticosteroid inhibition of adrenocorticotrophin release from the anterior pituitary gland of the rat

Abstract: The occurrence and nature of corticosteroid inhibition of ACTH secretion at the rat anterior pituitary gland was investigated using three experimental models: animals bearing lesions of the basal hypothalamus, and two preparations of the gland incubated in vitro; these were tissue segments and collagenase-dispersed cells. Release of ACTH in the experiments was provoked using one of three distinct stimuli: acid extracts of whole hypothalami, corticotrophin releasing activity released by serotonin from hypothala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 13 publications
1
25
1
Order By: Relevance
“…As far as the anterior pituitary gland is concerned, 17a-OH-progesterone has no antagonistic effect on the early delayed feedback action of corticosteroids on the re sponse of mediobasal hypothalamic-lesioned rats to injec tion of hypothalamic extract [19]. The present results also show that the combination of the two steroids is ineffective in counteracting the inhibitory effects of corticosterone on subsequent in vitro responsiveness to AVP or CRF-4I at the anterior pituitary level.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…As far as the anterior pituitary gland is concerned, 17a-OH-progesterone has no antagonistic effect on the early delayed feedback action of corticosteroids on the re sponse of mediobasal hypothalamic-lesioned rats to injec tion of hypothalamic extract [19]. The present results also show that the combination of the two steroids is ineffective in counteracting the inhibitory effects of corticosterone on subsequent in vitro responsiveness to AVP or CRF-4I at the anterior pituitary level.…”
Section: Discussioncontrasting
confidence: 41%
“…The fact that the combination of these antagonists effectively block the early delayed effects of a variety of feedback agonists in vivo implies that inhibition of ACTH secretion from the pituitary gland can be over-ridden by an increase in CRF-AVP drive from the hypothalamus. We have previ ously shown that feedback at the pituitary level can be over come by increasing the ACTH-releasing stimulus [19]. Therefore the sites of action of the antagonistic steroids must be located either in the hypothalamus or at extrahypothalamic sites.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with elevated circulating corticosterone levels following noise exposure, marked strain differences were evident with respect to interstitial levels of corticosterone at the anterior pituitary, with noise exposure markedly elevating corticosterone availability in the Fischer, but not in the Lewis rats. Corticosterone-induced suppression of the HPA axis occurs both at pituitary and suprapituitary levels (Mahmoud et al, 1984;Widmaier and Dallman, 1984). The finding that male Fischer and Lewis rats display similar sensitivity to peripherally administered dexamethasone (Gomez et al, 1998) suggests similar glucocorticoid receptor function between these strains.…”
Section: Discussionmentioning
confidence: 98%
“…This time delay of a few minutes is presumably due to the time needed by the adrenal for de novo synthesis CORT in response to ACTH, since in contrast to peptides hormones (e.g., CRH and ACTH), CORT cannot be pre-synthesized and stored within adrenal steroidogenic cells due to its lipophilic nature. Once released into the general circulation, CORT activates a fast (presumably non-genomic) negative feedback mechanism at the level of the pituitary that still remains to be fully characterized (Jones et al 1972, 1974, Rotsztejn et al 1975a,b, Mahmoud et al 1984, Widmaier & Dallman 1984, Hinz & Hirschelmann 2000, Russell et al 2010.…”
Section: The Origin Of Glucocorticoid Pulsatilitymentioning
confidence: 99%